Reformulation of Islamic Boarding School Education Management Through Islamic Counseling Service in Facing the Challenge of Globalization - Asep Rohani; Hidayatul Faridah; Feri Hardiyanto (Indonesian Journal of Multidisciplinary Science, 2026)
This study aims to reformulate Islamic boarding school education management through the integration of Islamic counseling services in responding to the challenges of globalization. Pesantren, as one of Indonesia's oldest educational institutions, is currently facing rapid social and cultural transformations driven by digitalization, global mobility, and moral disruption. To address these challenges, a mixed-method multi-phase design was employed. In the first phase, qualitative exploration through interviews, focus group discussions, and document analysis was conducted to map the needs and obstacles in managing counseling services. The second phase utilized the Delphi technique involving experts in Islamic counseling, education management, and Islamic boarding school leadership to construct and validate a comprehensive management model. The third phase implemented a quasi-experimental design with pretest–posttest control groups to test the effectiveness of the model in enhancing resilience, global competence, and ethical digital behavior among santri. The results show that the reformulated management model successfully improves the role of Islamic counseling services in Islamic boarding schools by integrating policy planning, organizational structure, service delivery, and monitoring evaluation mechanisms. This model is proven effective in strengthening santri's resilience and digital ethics while reducing cases of bullying and maladaptive behavior. The study concludes that Islamic boarding school management needs to institutionalize Islamic counseling as a strategic component to ensure the sustainability of character education and competitiveness of Islamic boarding school graduates in the era of globalization.